2004
DOI: 10.1002/art.20235
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and quality of life in patients with acute low back pain: Insights from a comprehensive inception cohort study

Abstract: Objective. To investigate the respective contribution of various biologic and psychosocial factors, especially initial health-related quality of life (HRQOL), in the natural history of acute low back pain (LBP) and to evaluate the impact of this condition on HRQOL. Methods. For 3 months, we assessed 113 patients consulting for nonspecific acute LBP of <72 hours duration at inclusion and treated with acetaminophen. Endpoints included pain, disability assessed by the Roland Disability Questionnaire, and HRQOL as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 35 publications
5
39
0
3
Order By: Relevance
“…However, our current results suggest that some of the strongest predictors of persistence are measures of symptom severity and duration. These results are similar to those from recent adult studies that found that episode-specific factors, such as duration of symptoms, were associated with poor prognosis (26,27,37). It is intuitive that symptoms of longer initial duration are more likely to be persistent.…”
Section: Discussionsupporting
confidence: 90%
“…However, our current results suggest that some of the strongest predictors of persistence are measures of symptom severity and duration. These results are similar to those from recent adult studies that found that episode-specific factors, such as duration of symptoms, were associated with poor prognosis (26,27,37). It is intuitive that symptoms of longer initial duration are more likely to be persistent.…”
Section: Discussionsupporting
confidence: 90%
“…Only a small proportion of eligible studies explicitly excluded patients with leg pain or sciatica, 17,18 while most studies either did not provide any information on this distinction (12 cohorts) or included some patients with leg pain or sciatica (19 cohorts). It was common for authors to refer to the presence of leg pain as sciatica without differentiating whether the pain was somatic or radicular.…”
Section: Limitationsmentioning
confidence: 99%
“…Job dissatisfaction 21 , previous sick leave for LBP 5 , somatic distress 22,23 , depression 24,25,26 27,28,29 , fear of movement 17 and passive coping 23,30 have all been shown to predict long-term status when measured at baseline. We assessed patients' anxiety, somatic distress, depression and mental well-being at baseline and found little of importance in determining long-term pain or disability with these measures.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%